(untitled) (Global Journal of Human-Social Science, 2024)
It analyzes the expansion of the agricultural frontier and extractivist economies in the Southwestern Amazon, where the social and environmental impacts predominantly affect protected territories and rural communities. Based on the concepts of land conflicts and agribanditry, this analysis evaluates the forces of neoextractivist capital, which are intertwined with agribusiness policies that primarily weaken environmental regulations and territorial rights to concentrate public lands, leading to the deterritorialization of Amazonian peoples and the regional peasantry.